Captivity-induced metabolic programming in an endangered felid: implications for species conservation - Reeves, Jessica; Smith, Carl; Dierenfeld, Ellen S; Whitehouse-Tedd, Katherine (Scientific reports, 2020)
Reintroduction of captive-bred individuals into the wild is an important conservation activity. However, environmental conditions can influence developmental programming, potentially causing metabolic disorders in adults. These effects are investigated here for the first time in an endangered species. Using body weight and feed intake data for Iberian lynx (Lynx pardinus) (n = 22), we compared the growth of captive versus wild born and/or reared individuals. Captive-born individuals gained weight as a function of calorie intake, unlike wild-born individuals. When compared with females reared in the wild, captive-reared females achieved a larger body size, without evidence of obesity. Captivity-associated changes to metabolic programming may compromise survival in the wild if an increased body size incurs a greater energy requirement. Large body size may also confer a competitive advantage over smaller, wild-born individuals, disrupting the social organisation of existing wild populations, and inferring long-term implications for the phenotypic composition of wild populations.
Keywords: Lynx; Conservation of Natural Resources; Body Weight; Behavior, Animal; zvířata; Animals; zachování přírodních zdrojů; Female; Male; ohrožené druhy; Endangered Species; mužské pohlaví; ženské pohlaví; Social Behavior; sociální chování; chování zvířat; Energy Intake; tělesná hmotnost; Social Isolation; energetický příjem; sociální izolace